Integrated antenna for V2X applications - Lee, Jun Jie (2019)
The demand for more compact and integrated antennas. for Vehicle-to-Everything (V2X) communication, is growing as the world shifts their focus in an Intelligent Transport System (ITS). In this project, an integrated antenna will be developed for a specific form of transport, which is the Personal Mobility Device (PMD). The two most used PMDs are the e-scooter, as well as the bicycle. The aim of this final year project is to understand the theory of antenna design and utilise the technical knowledge to design a conformal multi-band antenna. The proposed antenna is a cylindrical shaped structure which consists of; a ground plan on the innermost layer, surrounded by a layer of dielectric substrate (Teflon), and separate microstrip patch antennas for different frequency ranges mounted onto the substrate. The structure of the proposed antenna is modelled using the ANSYS High Frequency Structure Simulator (HFSS) software. A return loss of -21.6045dB was recorded at a lower band frequency of 2.1GHz, with a frequency range of 2.04GHz to 2.16GHz at the -10dB point. As for the higher band frequency of 5.9GHz, the recorded return loss was -14.2236dB, with a frequency range of 5.77GHz to 5.94GHz at the -10dB point. As for the gain, the highest gain value recorded at 2.1GHz is 2.3638dBi, and 6.5949dBi at 5.9GHz. Impedance values of the antenna at 2.1GHz is Re = 51.42Ω, and Im = 8.34Ω, and Re = 70.82Ω, and Im = 11.10Ω at 5.9GHz. In this final year project, different antenna design parameters, which will be covered in the literature review, were studied to achieve optimal results of the antenna performance. The results obtained from the simulations on HFSS will then be analysed and discussed. Following the software simulation design, the finalized designed antenna was then fabricated and tested for its radiation properties.